Peran Nurcholish Madjid dalam Perkembangan Pemikiran Noe-Modernisme Islam Indonesia, 1966-2005 - Faiqbal Latif (Universitas Hamzanwadi, 2022)
The development of Islamic thought is part of history that builds civilization, because not infrequently thought is the beginning of the development of world civilization which is built through awareness. Islamic Neo-Modernism is a school of renewal of thought that responds to challenges and previous thoughts (traditionalism and modernism). Nurcholish Madjid became an intellectual who gave a new color to the presence and development of Islamic Neo-Modernism in Indonesia. The purpose of this research is to find out how the development of Neo-Modernism thought brought by Nurcholish in Indonesia with the period of his active period until his death (1966-2005) and its influence in Indonesia. This study uses the historical method, where the source of the data obtained comes from literature studies. The results of this study are the presence and development of Islamic Neo-Modernism in the world and in Indonesia, the evolution of Nurcholish Madjid's Neo-Modernism, and how it influences the world of thought in Indonesia.